Coated cutting tools

By providing a specific compound layer structure in the coating coated with the cutting tool, the problem of peeling caused by high compression stress of the hard film in the prior art is solved, and wear resistance and damage resistance are improved, and tool life is extended.

CN115637408BActive Publication Date: 2025-03-21TUNGALOY CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210614411.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-19
Filing Date
2022-06-01
Publication Date
2025-03-21
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

In the prior art, the crystal system of the hard film is cubic crystal, but the compression stress is high, resulting in peeling problems, making it difficult to thicken the coating, resulting in insufficient wear and damage resistance, and making it difficult to extend the tool life.

Method used

A specific compound layer structure is provided in the coating layer for coating the cutting tool. The composition of the compound layer is (AlxCryTi1﹣x﹣y)N, x is 0.70 or more, y is 0.04 or more, the Cr/Ti ratio is 1.0 or more, 2.5 or less, the average thickness of the compound layer is 2.0 μm or more, 10.0 μm or less, the residual stress is -10.0 GPa or more -2.0 GPa or less, the average particle diameter of the particles is 10 nm or more, and the compound layer is a columnar crystal structure.

Benefits of technology

Improves the wear resistance and damage resistance of coated cutting tools and extends the tool life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115637408B_ABST
    Figure CN115637408B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a coated cutting tool having improved wear resistance and breakage resistance and prolonged tool life. The coated cutting tool comprises a substrate and a coating formed on the substrate, wherein the coating has a compound layer comprising a compound, wherein the composition of the compound is (Al x Cr y Ti 1﹣x﹣y )N(in the formula, x represents the atomic ratio of Al element to the total amount of Al element, Cr element and Ti element, and satisfies 0.70≦x≦0.95; y represents the atomic ratio of Cr element to the total amount of Al element, Cr element and Ti element, and satisfies 0.04≦y≦0.21; in addition, 1-x-y>0), the ratio of Cr element to Ti element in the compound layer (Cr / Ti) is not less than 1.0 and not more than 2.5, and the average thickness of the compound layer is not less than 2.0μm and not more than 10.0μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coated cutting tool. Background Art

[0002] Cutting tools made of cemented carbide or cubic boron nitride (cBN) sintered bodies have been widely used in cutting of steel and other materials. Among them, surface-coated cutting tools (the surface of the cemented carbide substrate includes one or more hard coating films such as TiN layer, TiAlN layer, AlCrN layer, etc.) are used in various processes because of their high versatility.

[0003] Among them, a surface-coated cutting tool in which the atomic ratio of Al in the AlCrN layer is 70% or more contains hexagonal crystals, which results in a decrease in hardness and thus a decrease in wear resistance.

[0004] In order to improve this problem, for example, Patent Document 1 proposes a method for forming a hard film, wherein the hard film includes AlCrN or the like containing cubic crystals (with an Al atomic ratio of 80% or more). Specifically, the method for forming the hard film uses a cathode arc ion plating device, which contains AlCrN and AlCrN. x Cr y M z The target composition is (0.80≤x≤0.95, 0.05≤y+z≤0.20, z≤0.05: x, y, z represent the atomic ratios of Al, Cr, and M respectively. M represents any element among Ti, V, Zr, and Nb). The proposed method for forming a hard film is characterized in that the hard film is formed by setting the bias voltage range applied to the substrate arranged in the cathode arc ion plating device to -100V to -150V and the temperature range of the substrate to 330℃ to 370℃.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-109210

[0008] Technical issues

[0009] However, the hard film produced by the film forming method described in Patent Document 1 has a cubic crystal system, but the compressive stress is very high, and peeling occurs after the hard film is formed, and it is difficult to increase the thickness of the hard film. Therefore, the coated cutting tool with a hard film described in Patent Document 1 is insufficient in wear resistance, so it is difficult to extend the tool life.

[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coated cutting tool having improved wear resistance and breakage resistance and a prolonged tool life. Summary of the invention

[0011] The inventors have repeatedly studied how to extend the tool life of coated cutting tools and have discovered that by providing a specific structure for the coating in the coated cutting tool, the wear resistance and breakage resistance can be improved, thereby extending the tool life of the coated cutting tool, thereby completing the present invention.

[0012] That is, the gist of the present invention is as follows.

[0013] [1] A coated cutting tool comprising a substrate and a coating formed on the substrate, wherein the coating has a compound layer comprising a compound, wherein the composition of the compound is represented by the following formula (1):

[0014] (Al x Cr y Ti 1﹣x﹣y )N (1)

[0015] (In formula (1), x represents the atomic ratio of Al element to the total amount of Al element, Cr element and Ti element, and satisfies 0.70≦x≦0.95; y represents the atomic ratio of Cr element to the total amount of Al element, Cr element and Ti element, and satisfies 0.04≦y≦0.21; in addition, 1-x-y>0)

[0016] The ratio of Cr element to Ti element (Cr / Ti) in the compound layer is greater than 1.0 and less than 2.5;

[0017] The average thickness of the compound layer is 2.0 μm or more and 10.0 μm or less.

[0018] [2] The coated cutting tool according to [1], wherein the residual stress of the compound layer is -10.0 GPa or more and -2.0 GPa or less.

[0019] [3] The coated cutting tool according to [1] or [2], wherein the average particle size of the particles in the compound layer is from 10 nm to 300 nm.

[0020] [4] The coated cutting tool according to any one of [1] to [3], wherein in the compound layer, when the diffraction peak intensity of the cubic crystal (200) plane is I cub The diffraction peak intensity of (200) and (100) planes of hexagonal crystal is I hex (100) hex (100) / I cub (200) is less than 0.2.

[0021] [5] The coated cutting tool according to any one of [1] to [4], wherein the compound layer has a columnar crystal structure.

[0022] According to the present invention, it is possible to provide a coated cutting tool having improved wear resistance and breakage resistance and a prolonged tool life. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic diagram of an example of the coated cutting tool of the present invention. DETAILED DESCRIPTION

[0024] Below, a method for implementing the present invention (hereinafter referred to as "this embodiment") is described in detail, but the present invention is not limited to the following embodiment. The present invention can be modified in various ways without departing from the scope of its subject matter. It should be noted that in the accompanying drawings, the same symbols are marked for the same elements, and repeated descriptions are omitted. In addition, the positional relationships such as up and down, left and right, etc., are based on the positional relationships shown in the drawings unless otherwise specified. In addition, the dimensional ratios of the drawings are not limited to the illustrated ratios.

[0025] The coated cutting tool of the present embodiment comprises a substrate and a coating formed on the substrate. The coating has a compound layer (hereinafter, also referred to as a "compound layer") containing a compound, the composition of which is represented by the following formula (1):

[0026] (Al x Cr y Ti 1﹣x﹣y )N (1)

[0027] (In formula (1), x represents the atomic ratio of Al element to the total amount of Al element, Cr element and Ti element, and satisfies 0.70≦x≦0.95; y represents the atomic ratio of Cr element to the total amount of Al element, Cr element and Ti element, and satisfies 0.04≦y≦0.21; in addition, 1-x-y>0)

[0028] The ratio of Cr element to Ti element in the compound layer (Cr / Ti) is greater than 1.0 and less than 2.5;

[0029] The average thickness of the compound layer is 2.0 μm or more and 10.0 μm or less.

[0030] The main reason why the above-mentioned coated cutting tool can improve wear resistance and breakage resistance and extend tool life is not clear in detail. The present inventors believe that the main reason is as follows, but it is not limited to this. That is, in the compound layer forming the coating, when the composition of the compound (Al x Cr y Ti 1﹣x﹣y)N is 0.70 or more, the hardness becomes high, so the wear resistance of the coated cutting tool is improved. On the other hand, in the compound layer forming the coating, when the component of the compound (Al x Cr y Ti 1﹣x﹣y )N is 0.95 or less, the formation of the hexagonal crystal structure can be suppressed, the hardness becomes higher, and thus the wear resistance of the coated cutting tool is improved. In addition, in the compound layer forming the coating, when the component of the compound (Al x Cr y Ti 1﹣x﹣y )N is 0.04 or more, the high temperature strength of the compound layer is increased due to the inclusion of Cr and the formation of hexagonal crystals is suppressed, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the compound layer forming the coating, when the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N is less than 0.21, because it contains an appropriate amount of Cr, the high temperature strength is increased and cubic crystals are easily formed, so the hardness becomes higher, and the wear resistance of the coated cutting tool is improved. In addition, in the compound layer forming the coating, when the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N, when 1-x-y>0, the adhesion of the compound layer is improved due to the presence of Ti, so the chipping resistance and wear resistance of the coated cutting tool are improved. In addition, in the compound layer forming the coating, when the ratio of Cr element to Ti element (Cr / Ti) is greater than 1.0, the increase in the Cr ratio leads to an increase in high-temperature strength, and the decrease in the Ti element ratio can inhibit the formation of a hexagonal crystal structure. On the other hand, in the compound layer forming the coating, when the ratio of Cr element to Ti element (Cr / Ti) is less than 2.5, the adhesion of the compound layer is improved, so the chipping resistance and wear resistance are improved. In addition, when the average thickness of the compound layer forming the coating is greater than 2.0μm, the wear resistance of the coated cutting tool is improved. On the other hand, when the average thickness of the compound layer forming the coating is less than 10.0μm, the peeling of the coating can be suppressed, so the breakage resistance of the coated cutting tool is improved. These effects cooperate with each other, so that the wear resistance and breakage resistance of the coated cutting tool of this embodiment are improved, and the tool life is prolonged.

[0031] The coated cutting tool of the present embodiment comprises a substrate and a coating formed on the surface of the substrate. The substrate used in the present embodiment is not particularly limited, as long as it can be used as a substrate for a coated cutting tool. For example, examples of the substrate include cemented carbide, cermet, ceramic, cubic boron nitride sintered body, diamond sintered body and high-speed steel. Among them, if the substrate is one or more selected from the group consisting of cemented carbide, cermet, ceramic and cubic boron nitride sintered body, the damage resistance of the coated cutting tool is more excellent, so it is further preferred.

[0032] <Compound Layer>

[0033] In the coated cutting tool of the present embodiment, the coating layer has a compound layer containing a compound whose composition is represented by the following formula (1):

[0034] (Al x Cr y Ti 1﹣x﹣y )N (1)

[0035] (In formula (1), x represents the atomic ratio of Al element to the total amount of Al element, Cr element and Ti element, and satisfies 0.70≦x≦0.95; y represents the atomic ratio of Cr element to the total amount of Al element, Cr element and Ti element, and satisfies 0.04≦y≦0.21; in addition, 1-x-y>0)

[0036] In the compound layer forming the coating, when the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N is 0.70 or more, the hardness becomes high, so the wear resistance of the coated cutting tool is improved. On the other hand, in the compound layer forming the coating, when the component of the compound (Al x Cr y Ti 1﹣x﹣y ) When x in N is less than 0.95, the formation of the hexagonal crystal structure can be suppressed, and the hardness becomes higher, so the wear resistance of the coated cutting tool is improved. From the same point of view, the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N is preferably 0.70 to 0.93, and more preferably 0.75 to 0.90. In the compound layer forming the coating, when the component of the compound (Al x Cr y Ti 1﹣x﹣y)N is 0.04 or more, the high temperature strength of the compound layer is increased due to the inclusion of Cr and the formation of hexagonal crystals is suppressed, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the compound layer forming the coating, when the composition of the compound (Al x Cr y Ti 1﹣x﹣y ) When y in N is less than 0.21, the high temperature strength is increased due to the presence of an appropriate amount of Cr and cubic crystals are easily formed, thereby increasing the hardness and improving the wear resistance of the coated cutting tool. From the same perspective, the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N is preferably 0.07 to 0.21, and more preferably 0.07 to 0.15. In the compound layer forming the coating, when the component of the compound (Al x Cr y Ti 1﹣x﹣y )N, when 1-x-y>0, the adhesion of the compound layer is improved due to the presence of Ti, so the chipping resistance and wear resistance of the coated cutting tool are improved. In addition, in the compound layer forming the coating, the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N, 1-x-y, that is, the atomic ratio of the Ti element is preferably in the range of 0.03 to 0.21, and more preferably in the range of 0.03 to 0.15.

[0037] It should be noted that in the composition of the compound (Al x Cr y Ti 1﹣x﹣y )N, the sum of the atomic ratios of the Al element, the Cr element and the Ti element is 1.0.

[0038] In the coated cutting tool of the present embodiment, the ratio of Cr element to Ti element (Cr / Ti) in the compound layer forming the coating is greater than 1.0 and less than 2.5. In addition, in the compound layer forming the coating, when the ratio of Cr element to Ti element (Cr / Ti) is greater than 1.0, the high temperature strength increases due to the increase in the Cr ratio, and the Ti element ratio decreases, thereby suppressing the formation of a hexagonal crystal structure. On the other hand, in the compound layer forming the coating, when the ratio of Cr element to Ti element (Cr / Ti) is less than 2.5, the adhesion of the compound layer is improved, thereby improving the chipping resistance and wear resistance.

[0039] In addition, in this embodiment, when the composition of the compound is expressed as (Al 0.80 Cr 0.10 Ti 0.10)N, it means that the atomic ratio of Al element relative to the total amount of Al element, Cr element and Ti element is 0.80; the atomic ratio of Cr element relative to the total amount of Al element, Cr element and Ti element is 0.10; the atomic ratio of Ti element relative to the total amount of Al element, Cr element and Ti element is 0.10. That is, the content of Al element relative to the total amount of Al element, Cr element and Ti element is 80 atomic percent (atomic %); the content of Cr element relative to the total amount of Al element, Cr element and Ti element is 10 atomic %; the content of Ti element relative to the total amount of Al element, Cr element and Ti element is 10 atomic %.

[0040] In the coated cutting tool of the present embodiment, the average thickness of the compound layer forming the coating is greater than or equal to 2.0 μm and less than or equal to 10.0 μm. In addition, when the average thickness of the compound layer forming the coating is greater than or equal to 2.0 μm, the wear resistance of the coated cutting tool is improved. On the other hand, when the average thickness of the compound layer forming the coating is less than or equal to 10.0 μm, the peeling of the coating can be suppressed, and thus the breakage resistance of the coated cutting tool is improved. From the same point of view, the average thickness of the compound layer forming the coating is preferably greater than or equal to 2.0 μm and less than or equal to 8.5 μm, and more preferably greater than or equal to 3.0 μm and less than or equal to 8.5 μm.

[0041] In addition, the residual stress of the compound layer of the coated cutting tool of the present embodiment is preferably above -10.0 GPa and below -2.0 GPa. When the residual stress of the compound layer is above -10.0 GPa, the generation of cracks can be suppressed after the coating is formed, and the thickness of the coating can be thickened, so that the wear resistance of the coated cutting tool tends to improve. On the other hand, when the residual stress of the compound layer is below -2.0 GPa, due to the effect of compressive stress, the expansion of cracks can be suppressed, so that the breakage resistance of the coated cutting tool tends to improve. From the same point of view, the residual stress of the compound layer is more preferably above -9.8 GPa and below -2.2 GPa, and further preferably above -9.6 GPa and below -2.5 GPa.

[0042] The above-mentioned residual stress refers to the internal stress (intrinsic strain) remaining in the coating. The stress represented by the value of "-" (negative) is usually called compressive stress, and the stress represented by the value of "+" (positive) is called tensile stress. In the present embodiment, when representing the magnitude of the residual stress, the larger the value of "+" (positive), the larger the residual stress, and the larger the value of "-" (negative), the smaller the residual stress.

[0043] It should be noted that the residual stress can be measured by using the sin 2 The residual stress can be measured by the sin 2The ψ method measures the stress at any three points included in the cutting-related part (in order to represent the stress of the part, the above points are preferably at a distance of 0.5 mm or more from each other) and determines the residual stress by calculating the average value.

[0044] In addition, the average particle size of the particles in the compound layer of the coated cutting tool of the present embodiment is preferably greater than 10 nm and less than 300 nm. When the average particle size of the particles in the compound layer is greater than 10 nm, the compressive stress can be prevented from becoming too high, the peeling of the compound layer can be prevented, and the breakage resistance of the coated cutting tool tends to improve. On the other hand, when the average particle size of the particles in the compound layer is less than 300 nm, the hardness of the compound layer becomes higher, and the wear resistance of the coated cutting tool tends to improve. From the same point of view, the average particle size of the particles in the compound layer is more preferably greater than 12 nm and less than 295 nm, and further preferably greater than 14 nm and less than 292 nm.

[0045] In addition, in the coated cutting tool of this embodiment, the compound layer preferably has a columnar crystal structure. In the coated cutting tool of this embodiment, when the compound layer has a columnar crystal structure, the particles can be suppressed from falling off, and the coating can function for a long time, so that the wear resistance tends to be further improved.

[0046] It should be noted that in the present embodiment, the shape, aspect ratio and average particle size of the particles in the compound layer can be measured using a commercially available transmission electron microscope (TEM). Specifically, for example, a focused ion beam (FIB) device is first used to prepare a thin film sample with a cross section of the compound layer (a cross section in the same direction as when observing the coating thickness: a direction perpendicular to the substrate surface) as the observation surface. For the observation surface of the prepared sample, a scanning transmission electron image (STEM image) is taken. At this time, preferably, in the direction perpendicular to the substrate, the STEM image includes all areas occupied by the compound layer, and in the direction parallel to the substrate surface, the STEM image includes areas above 10.0 μm. In the photographed picture, the value of the axis of the direction parallel to the substrate surface among the particles constituting the compound layer of all particles present in the compound layer is taken as the particle size, and its average value is taken as the average particle size of the compound layer.

[0047] The aspect ratio in the compound layer is obtained as follows: In the crystal grains used to measure the average grain size, the value of the axis in the coating thickness direction is taken as the height of the crystal grain. The value obtained by dividing the height of the crystal grain by the grain size is the aspect ratio.

[0048] If the number of crystal grains with an aspect ratio of 2 or more in the compound layer measured by the above method is more than 50% of the total number of crystal grains, it is a columnar crystal structure. In addition, if the number of crystal grains with an aspect ratio of 2 or more in the compound layer measured by the above method is less than 50% of the total number of crystal grains, that is, if the number of crystal grains with an aspect ratio of less than 2 is more than 50% of the total number of crystal grains, it is a granular crystal structure.

[0049] In addition, in the compound layer coated on the cutting tool of the present embodiment, when the diffraction peak intensity of the cubic crystal (200) plane is I cub The diffraction peak intensity of (200) and (100) planes of hexagonal crystal is I hex (100), preferably, I hex (100) / I cub (200) is less than 0.2. In the compound layer, when I hex (100) / I cub When (200) is 0.2 or less, the formation of the hexagonal crystal structure can be suppressed, so that the hardness becomes higher, and the wear resistance of the coated cutting tool tends to improve. From the same point of view, in the compound layer, I hex (100) / I cub The lower the value of (200), the more preferred. hex (100) / I cub A low value of (200) means a high proportion of cubic crystals. hex (100) / I cub The lower limit of the value of (200) is not particularly limited, and may be 0, for example.

[0050] In this embodiment, the peak intensity of each crystal plane of the compound layer can be measured by using a commercially available X-ray diffraction device. For example, using an X-ray diffraction device of model RINT TTRIII manufactured by Rigaku Co., Ltd., an X-ray diffraction measurement using a 2θ / θ focusing method optical system of Cu-Kα rays is performed under the following conditions to measure the peak intensity of each crystal plane. The above conditions are: output power: 50kV, 250mA; incident side Soller slit: 5°; divergent longitudinal slit: 2 / 3°; divergent longitudinal limit slit: 5mm; scattering slit: 2 / 3°; light receiving side Soller slit: 5°; light receiving slit: 0.3mm; BENT monochromator; light receiving monochromatic slit: 0.8mm; sampling width: 0.01°; scanning speed: 4° / min; 2θ measurement range: 20 to 50°. When obtaining the peak intensity of each crystal plane based on the X-ray diffraction pattern, the analysis software attached to the X-ray diffraction device can also be used. In the analysis software, the background processing and Kα2 peak removal can be performed by using cubic spline approximation, and the peak shape fitting (profile fitting) can be performed using the Pearson-VII function to obtain the intensity of each peak. It should be noted that in the case where various layers are formed between the compound layer and the substrate, in order not to be affected by these layers, the intensity of each peak can be measured by a thin film X-ray diffraction method. In addition, in the case where various layers are formed on one side of the compound layer opposite to the substrate side, the various layers can be removed by polishing (buffing), and then the X-ray diffraction measurement can be performed. In addition, in this embodiment, the crystal system of the compound layer can be determined by X-ray diffraction measurement.

[0051] Figure 1 1 is a schematic cross-sectional view of an example of a coated cutting tool according to the present embodiment. The coated cutting tool 3 includes a substrate 1 and a coating layer 2 formed on the surface of the substrate 1 .

[0052] <Lower floor>

[0053] The coating used in this embodiment may be composed only of a compound layer, but preferably, there is a lower layer between the substrate and the compound layer. This can further improve the adhesion between the substrate and the compound layer. Among them, from the same perspective as above, it is more preferred that the lower layer includes a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and at least one element selected from the group consisting of C, N, O and B. More preferably, the lower layer includes a compound consisting of at least one element selected from the group consisting of Ti, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and at least one element selected from the group consisting of C, N, O and B. Further preferably, the lower layer includes a compound consisting of at least one element selected from the group consisting of Ti, Ta, Cr, W, Al, Si and Y and N. In addition, the lower layer can be a single layer, or it can be two layers or more than two layers.

[0054] In this embodiment, when the average thickness of the lower layer is 0.1 μm to 3.5 μm, the adhesion between the substrate and the coating tends to be further improved, so this thickness range is more preferred. From the same perspective, more preferably, the average thickness of the lower layer is 0.2 μm to 3.0 μm, and further preferably, the average thickness of the lower layer is 0.3 μm to 2.5 μm.

[0055] <Upper layer>

[0056] In the coating used in the present embodiment, an upper layer is provided on the side of the compound layer opposite to the substrate (i.e., the upper layer of the compound layer), preferably, on the surface of the compound layer. When the upper layer includes a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and at least one element selected from the group consisting of C, N, O and B, the wear resistance is more excellent and further preferred. From the same perspective as above, it is more preferred that the upper layer includes a compound consisting of at least one element selected from the group consisting of Ti, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and at least one element selected from the group consisting of C, N, O and B. It is further preferred that the upper layer includes a compound consisting of at least one element selected from the group consisting of Ti, Nb, Ta, Cr, W, Al, Si and Y and N. In addition, the upper layer may be a single layer, or may be two layers or more.

[0057] In this embodiment, when the average thickness of the upper layer is 0.1 μm to 3.5 μm, the wear resistance tends to be further excellent, so this thickness range is more preferred. From the same perspective, more preferably, the average thickness of the upper layer is 0.2 μm to 3.0 μm, and further preferably, the average thickness of the upper layer is 0.3 μm to 2.5 μm.

[0058] <Coating preparation method>

[0059] The method for preparing the coating in the coated cutting tool of the present embodiment is not particularly limited, and may be, for example, a physical vapor deposition method such as an ion plating method, an arc ion plating method, a sputtering method, and an ion mixing method. When the physical vapor deposition method is used to form the coating, a sharp edge can be formed, so it is preferred. Among them, the arc ion plating method makes the adhesion between the coating and the substrate more excellent, so it is more preferred.

[0060] <Method for manufacturing coated cutting tool>

[0061] The method for manufacturing the coated cutting tool of the present embodiment will be described below using a specific example. It should be noted that the method for manufacturing the coated cutting tool of the present embodiment is not particularly limited as long as the structure of the coated cutting tool can be realized.

[0062] First, the substrate processed into a tool shape is placed in a reaction vessel of a physical vapor deposition device, and a metal evaporation source is placed in the reaction vessel. Then, the reaction vessel is evacuated until the pressure reaches 1.0×10 ﹣2 Pa, and the substrate is heated to a substrate temperature of 200°C to 700°C by a heater in the reaction container. After heating, Ar gas is introduced into the reaction container to make the pressure in the reaction container 0.5Pa to 5.0Pa. In an Ar gas environment with a pressure of 0.5Pa to 5.0Pa, a bias voltage of -500V to -350V is applied to the substrate, a current of 40A to 50A flows through the tungsten filament in the reaction container, and the surface of the substrate is subjected to ion bombardment treatment using Ar gas. After the surface of the substrate is subjected to ion bombardment treatment, the reaction container is evacuated until its pressure reaches 1.0×10 ﹣2 Vacuum below Pa.

[0063] When forming the lower layer used in the present embodiment, the substrate is heated until the substrate temperature reaches 400°C to 600°C. After heating, a gas is introduced into the reaction container so that the pressure in the reaction container is 0.5Pa to 5.0Pa. For example, in the case where the lower layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and a compound composed of N, the gas may be, for example, N2 gas; in the case where the lower layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and a compound composed of N and C, the gas may be, for example, a mixed gas of N2 gas and C2H2 gas. The volume ratio of the mixed gas is not particularly limited, for example, it may be N2 gas:C2H2 gas = 95:5 to 85:15. Subsequently, a bias voltage of -80V to -40V is applied to the substrate, and arc discharge with an arc current of 100A to 200A is performed to evaporate a metal evaporation source corresponding to the metal component of the lower layer to form the lower layer.

[0064] When forming the compound layer used in this embodiment, the substrate is controlled so that the substrate temperature reaches 200°C to 300°C, nitrogen (N2) is introduced into the reaction container, and the pressure in the reaction container is set to 8.0 Pa to 10.0 Pa. Then, a bias voltage of -400V to -200V is applied to the substrate, and a metal evaporation source corresponding to the metal component of the compound layer is evaporated by arc discharge of 100A to 200A, thereby forming a compound layer. By adjusting the arc discharge time of the metal evaporation source, the thickness of the compound layer can be controlled.

[0065] In order to make the X-ray diffraction intensity in the compound layer used in this embodiment higher than I hex (100) / I cub (200) is a specified value. In the process of forming the above compound layer, the temperature of the substrate is adjusted, the bias voltage is adjusted, the atomic ratio of each metal element is adjusted, or the pressure in the reaction container is adjusted. More specifically, in the process of forming the compound layer, if the temperature of the substrate is lowered (below 300°C) or the negative bias voltage is increased (away from 0), I hex (100) / I cub (200) tends to become smaller. In addition, in the process of forming the compound layer, if the atomic ratio of the Al element is reduced and the atomic ratio of the Cr element is increased, I hex (100) / I cub (200) tends to become smaller. In addition, if the ratio of the Cr element atomic ratio to the Ti element atomic ratio (Cr / Ti) is increased, I hex (100) / I cub(200) tends to become smaller. In addition, during the process of forming the compound layer, if the pressure in the reaction container is increased (above 8.0 Pa), I hex (100) / I cub (200) tends to become smaller.

[0066] In order to make the structure in the compound layer used in the present embodiment a columnar crystal structure, in the process of forming the above-mentioned compound layer, the temperature of the substrate is adjusted, or the bias voltage is adjusted. More specifically, in the process of forming the compound layer, if the temperature of the substrate is lowered (below 300°C) or the negative bias voltage is increased (in the direction away from 0), the structure in the compound layer tends to be a columnar crystal structure. In addition, if the average particle size of the particles in the compound layer is too small, the aspect ratio of the particles is easily less than 2, and the structure in the compound layer tends to be a granular crystal structure. In addition, in the process of forming the compound, if the atomic ratio of the Al element is increased too much, or the atomic ratio of the Cr element is reduced too much or the atomic ratio of the Cr element is not included, the structure in the compound layer tends to be a columnar crystal structure.

[0067] In order to make the average particle size of the particles in the compound layer used in this embodiment a specified value, in the process of forming the above-mentioned compound layer, the temperature of the substrate is adjusted, the bias voltage is adjusted, or the atomic ratio of each metal element is adjusted. More specifically, in the process of forming the compound layer, if the temperature of the substrate is increased or the negative bias voltage is reduced (closer to the 0 side), the average particle size of the particles in the compound layer tends to become smaller. In addition, in the process of forming the compound layer, if the atomic ratio of the Ti element is increased or the atomic ratio of the Al element is increased, the average particle size of the particles in the compound layer tends to become smaller.

[0068] In order to make the residual stress in the compound layer used in the present embodiment a specified value, in the process of forming the above-mentioned compound layer, the reaction container is set to a nitrogen (N2) environment, and the pressure is adjusted, the temperature of the substrate is adjusted, or the bias voltage is adjusted. More specifically, in the process of forming the compound layer, if the reaction container is set to a nitrogen (N2) environment, and the pressure in the reaction container is increased (8.0 Pa or more), the temperature of the substrate is increased, or the negative bias voltage is reduced (close to 0 side), the residual stress in the compound layer tends to increase.

[0069] When forming the upper layer used in the present embodiment, it can be formed by the same preparation conditions as the above-mentioned lower layer. That is, first, the substrate is heated until the substrate temperature reaches 400°C to 600°C. After heating, a gas is introduced into the reaction container so that the pressure in the reaction container is 0.5Pa to 5.0Pa. For example, in the case where the upper layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y and a compound composed of N, the above-mentioned gas can be, for example, N2 gas; in the case where the upper layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and a compound composed of N and C, the above-mentioned gas can be, for example, a mixed gas of N2 gas and C2H2 gas. The volume ratio of the mixed gas is not particularly limited, for example, it can be N2 gas: C2H2 gas = 95:5 to 85:15. Subsequently, a bias voltage of -80V to -40V is applied to the substrate, and arc discharge with an arc current of 100A to 200A is performed to evaporate a metal evaporation source corresponding to the metal component of the upper layer to form the upper layer.

[0070] The thickness of each layer constituting the coating in the coated cutting tool of the present embodiment can be measured from the cross-sectional structure of the coated cutting tool using an optical microscope, a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc. It should be noted that the average thickness of each layer in the coated cutting tool of the present embodiment can be obtained by measuring the thickness of each layer in three or more cross sections from the edge line of the blade of the surface opposite to the metal evaporation source toward the center of the surface at a position of 50 μm, and calculating the average value (arithmetic mean).

[0071] In addition, the composition of each layer constituting the coating in the coated cutting tool of this embodiment can be measured from the cross-sectional structure of the coated cutting tool of this embodiment using an energy dispersive X-ray analyzer (EDS) or a wavelength dispersive X-ray analyzer (WDS).

[0072] Since the coated cutting tool of this embodiment is excellent in at least wear resistance and breakage resistance, it can extend the tool life compared with the past (however, the main reason for extending the tool life is not limited to the above reasons). The types of coated cutting tools of this embodiment can be, for example, head-replaceable cutting inserts, drills, and end mills used for milling or turning.

[0073] Example

[0074] Hereinafter, the present invention will be further described in detail by way of examples, but the present invention is not limited to these examples.

[0075] (Example 1)

[0076] A blade of SWMT13T3AFPR-MJ (manufactured by TUNGALOY Co., Ltd.) (hard alloy having a composition of 89.8% WC-9.8% Co-0.4% Cr3C2 (mass %)) was prepared as a substrate. A metal evaporation source was arranged in a reaction vessel of an arc ion plating device to obtain a composition of a compound layer as shown in Table 1. The prepared substrate was fixed to a fixed support of a rotating table in the reaction vessel.

[0077] Then, the reaction vessel was evacuated until the pressure reached 5.0×10 -3 After evacuation, the substrate was heated by a heater in the reaction container until the substrate temperature reached 450° C. After heating, Ar gas was introduced into the reaction container to make the pressure 2.7 Pa.

[0078] In an Ar gas environment with a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction container, and the surface of the substrate was bombarded with Ar gas for 30 minutes. After the ion bombardment treatment was completed, the reaction container was evacuated until the pressure reached 5.0×10 ﹣3 Vacuum below Pa.

[0079] For the invention products 1 to 19 and the comparative products 1 to 10, after evacuation, the substrate temperature is controlled to be the temperature shown in Table 2 (the temperature at the start of film formation), nitrogen (N2) is introduced into the reaction container, and the pressure in the reaction container is adjusted to the pressure shown in Table 2. Then, the bias voltage shown in Table 2 is applied to the substrate, and the metal evaporation source of the compound layer of the components shown in Table 1 is evaporated by arc discharge with the arc current shown in Table 2 to form a compound layer on the surface of the substrate. At this time, the pressure in the reaction container is controlled to be the pressure shown in Table 2. In addition, the arc discharge time of each is adjusted and controlled so that the thickness of the compound layer reaches the thickness shown in Table 1.

[0080] A compound layer having a predetermined average thickness shown in Table 1 was formed on the surface of the substrate, and then the power supply to the heater was turned off. After the sample temperature reached 100° C. or less, the sample was taken out from the reaction container.

[0081] Table 1

[0082]

[0083] Table 2

[0084]

[0085] The average thickness of the compound layer of the obtained sample was obtained by measuring the thickness of the compound layer by performing TEM observation on three cross sections at a position of 50 μm from the blade edge line of one side of the coated cutting tool opposite to the metal evaporation source toward the center of the surface, and calculating the average value (arithmetic mean). The results are shown in Table 1.

[0086] The composition of the compound layer of the obtained sample was measured using EDS attached to TEM in a cross section from the blade edge portion of one side of the coated cutting tool opposite to the metal evaporation source toward the center portion to a position near 50 μm. The results are also shown in Table 1. It should be noted that the composition ratio of the metal elements in the compound layer in Table 1 represents the atomic ratio of each metal element in the metal compound constituting the compound layer relative to the entire metal element.

[0087] <I hex (100) / I cub (200)>

[0088] The ratio I in the obtained sample compound layer hex (100) / I cub (200) was measured using an X-ray diffraction device model RINT TTRIII manufactured by Rigaku Co., Ltd. Specifically, the peak intensity I of the (200) plane of the compound layer was measured under the following conditions: cub The peak intensity I of the (200) and (100) planes of the compound layer hex (100) X-ray diffraction measurement was performed using a Cu-Kα ray 2θ / θ focusing method optical system, and the ratio I was calculated. hex (100) / I cub (200). The above conditions are: output power: 50kV, 250mA; incident side Soller slit: 5°; divergent longitudinal slit: 2 / 3°; divergent longitudinal limit slit: 5mm; scattering slit: 2 / 3°; receiving side Soller slit: 5°; receiving slit: 0.3mm; BENT monochromator; receiving monochromatic slit: 0.8mm; sampling width: 0.01°; scanning speed: 4° / min; 2θ measurement range: 20~50°. hex (100) / I cub The results of (200) are shown in Table 3. In addition, the crystal system of the compound layer can also be determined by X-ray diffraction measurement.

[0089] <Residual stress>

[0090] The obtained sample was analyzed by using the sin 2The residual stress of the compound layer was measured by the ψ method. For the residual stress, the stress of any three points included in the cutting-related part was measured, and the average value (arithmetic mean) was taken as the residual stress of the compound layer. The results are shown in Table 3.

[0091] <Particle shape, aspect ratio and average particle size>

[0092] The shape, aspect ratio and average particle size of the particles in the compound layer of the obtained sample are measured using a commercially available transmission electron microscope (TEM). Specifically, for example, a focused ion beam (FIB) device is first used to prepare a thin film sample with a cross section of the compound layer (a cross section in the same direction as when observing the coating thickness: a direction perpendicular to the substrate surface) as the observation surface. For the observation surface of the prepared sample, a scanning transmission electron image (STEM image) is taken. At this time, in the direction perpendicular to the substrate, the STEM image includes all areas occupied by the compound layer, and in the direction parallel to the substrate surface, the STEM image includes an area of ​​10.0 μm. In the photographed image, the value of the axis in the direction parallel to the substrate surface among the particles constituting the compound layer of all particles existing in the compound layer is taken as the particle size, and the average value thereof is taken as the average particle size of the compound layer.

[0093] The aspect ratio in the compound layer is obtained as follows: In the crystal grains used to measure the average grain size, the value of the axis in the coating thickness direction is taken as the height of the crystal grain. The value obtained by dividing the height of the crystal grain by the grain size is the aspect ratio.

[0094] If the number of crystal grains with an aspect ratio of 2 or more in the compound layer measured by the above method is more than 50% of the total number of crystal grains, it is a columnar crystal structure. In addition, if the number of crystal grains with an aspect ratio of 2 or more in the compound layer measured by the above method is less than 50% of the total number of crystal grains, that is, if the number of crystal grains with an aspect ratio of less than 2 is more than 50% of the total number of crystal grains, it is a granular crystal structure. The results of the shape of each specific particle and the average particle size are shown in Table 3.

[0095] Table 3

[0096]

[0097] The obtained samples were used to perform the following cutting test and evaluate.

[0098] <Cutting test>

[0099] Cutting material: FCD600;

[0100] Shape of the material being cut: 60mm×100mm×200mm plate;

[0101] Cutting speed: 150m / min;

[0102] Feed per tooth: 0.2mm / tooth;

[0103] Cutting depth: 2.0mm;

[0104] Cutting width: 100mm;

[0105] Coolant: Dry (not used);

[0106] Evaluation items: The tool life is defined as the time until the sample is cracked (width of 0.2 mm or more) or damaged, and the processing time until the tool life is measured. It should be noted that this cutting test is carried out under processing conditions that are difficult to cause sudden damage, etc. As the side of the sample wears, the strength of the cutting edge is insufficient, resulting in cracking or damage. Therefore, the longer the processing time until the tool life, the better the damage resistance and wear resistance, especially the better the wear resistance. The evaluation results are shown in Table 4.

[0107] Table 4

[0108]

[0109] According to the results shown in Table 4, the processing time of the invention product is 80 minutes or more, which is longer than the processing time of all the comparative products.

[0110] From the above results, it can be seen that the tool life of the invention product can be extended by improving wear resistance and breakage resistance.

[0111] Industrial Applicability

[0112] The coated cutting tool of the present invention has excellent wear resistance and breakage resistance, and can extend the tool life compared with the related art. In this respect, the coated cutting tool of the present invention has high industrial applicability.

[0113] Main component symbols

[0114] 1…substrate, 2…coating, 3…coated cutting tool.

Claims

1. A coated cutting tool comprising a substrate and a coating formed on the substrate, The coating layer has a compound layer containing a compound, and the composition of the compound is represented by the following formula (1): (Al x Cr y Ti 1﹣x﹣y )N formula (1) In the formula (1), x represents the atomic ratio of Al element to the total amount of Al element, Cr element and Ti element, and satisfies 0.79≦x≦0.95; y represents the atomic ratio of Cr element to the total amount of Al element, Cr element and Ti element, and satisfies 0.04≦y≦0.15; 1-x-y>0; The ratio of Cr element to Ti element (Cr / Ti) in the compound layer is greater than 1.0 and less than 2.5; The average thickness of the compound layer is not less than 2.0 μm and not more than 10.0 μm; The average particle size of the particles in the compound layer is not less than 10 nm and not more than 300 nm; The compound layer has a columnar crystal structure; The coated cutting tool also includes a lower layer located between the substrate and the coating, and an upper layer located on the side of the coating away from the substrate; the lower layer includes a compound composed of at least one element selected from the group consisting of Ti, Ta, Cr, W, Al, Si and Y, and N, and the average thickness of the lower layer is greater than 0.1 μm and less than 3.5 μm; the upper layer includes a compound composed of at least one element selected from the group consisting of Ti, Nb, Ta, Cr, W, Al, Si and Y, and N, and the average thickness of the upper layer is greater than 0.1 μm and less than 3.5 μm.

2. The coated cutting tool according to claim 1, wherein: The residual stress of the compound layer is not less than -10.0 GPa and not more than 2.0 GPa.

3. The coated cutting tool according to any one of claims 1 to 2, wherein: In the compound layer, when the diffraction peak intensity of the cubic crystal (200) plane is I cub The diffraction peak intensity of (200) and (100) planes of hexagonal crystal is I hex (100) hex (100) / I cub (200) is less than 0.2.

Citation Information

Patent Citations

  • Film deposition method of hard film

    JP2020109210A